Representasi Gaya Bahasa Sindiran pada Webtoon Trickster sebagai Media Pembelajaran Komik Strip Teks Anekdot di SMA - Imatriya Nur Jannah; Jendriadi; Yanti Sariasih (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
Satire language style in literary works can be used as a medium for conveying social criticism. The purpose of this study is to identify and analyze the satire used in the Webtoon "Trickster" and then apply these findings to learning problems. The goal is to facilitate students understanding, particularly of social criticism in anecdotal texts. This study employed a qualitative descriptive method. Data were collected using simak and catat techniques through documentation studies. The simak technique involved analyzing comic panels, including visuals, dialogue bubbles, and narrative elements. The catat technique served as a follow-up to the data collected through simak techniques. The data analysis process included data reduction, data presentation, conclusions, and data verification. The results of this study revealed the satire in the Webtoon "Trickster" and the social criticism it contains. These satire styles are grouped into four types: irony, cynicism, sarcasm, and satire. Although numerous studies have addressed the issue of figurative language, there are still few that specifically link it to social criticism and use webtoons as a medium for application.